Use of laryngeal mask airway in flexible bronchoscopy in children - Arican, Sule; Pekcan, Sevgi; Hacibeyoglu, Gulcin; Tavlan, Aybars; Atay, Turgay; Kolsuz Erdem, Feyza; Tuncer Uzun, Sema (Annals of Medical Research, 2021)
Aim: Flexible bronchoscope is widely used by pediatric pulmonologists as a diagnostic and therapeutic tool. The objective of this study was to present our anesthesia experience in pediatric flexible bronchoscopy in which airway management was provided with laryngeal mask airway (LMA) and the complications developed.Material and Methods: This study was conducted in children aged between 2-15 years who underwent bronchoscopy for diagnosis and/or treatment between January 2017 and November 2018. Patients’ demographic data, diagnosis, anesthesia and airway management were recorded from the patient files. Times of anesthesia, operation and recovery were recorded. Complications during the procedure, awakening and recovery were recorded. Patients’ sore throat and hoarseness during resting and swallowing were recorded. Results: This study included 31 patients whose airway management was provided with LMA. The mean age was 8.58±4.14 years. Persistent cough was the most common indication for bronchoscopy (35.5%). Anesthesia time was 15.46±10.99 minutes, bronchoscopy time 12.87±10.57, awakening time 16.38±4.53 minutes, and recovery time 23.32±10.24 minutes. The most common complication was cough (45.2%). Sore throats of the patients were observed as mild and moderate at the 0th and 2th hours. Both resting and swallowing sore throats were observed as mild at the 4th hour, while no sore throat was seen in any patient at the 12th hour. Hoarseness was observed at mild level in 4 patients (12.9%) at the 0th hour.Conclusion: Providing airway with LMA in pediatric flexible bronchoscopy applications offers a safe anesthetic management, and it has a low rate of complications.Keywords: Flexible bronchoscopy; pediatric bronchoscopy; laryngeal mask airway.
Keywords: Flexible bronchoscopy; pediatric bronchoscopy; laryngeal mask airway.